2018
DOI: 10.3389/fphar.2018.01095
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Anti-migraine Effects of Valproic Acid and Topiramate in Rats

Abstract: Background: Valproic acid (VPA) and topiramate (TPM), initially developed as antiepileptics, are approved for migraine prophylaxis in adults but not children. The differences in their antimigraine mechanism(s) by age remain unclear.Methods: A migraine model induced by intra-cisternal (i.c.) capsaicin instillation in pediatric (4–5 weeks) and adult (8–9 weeks) rats was pretreated with VPA (30, 100 mg/kg) or TPM (10, 30, 100 mg/kg). Noxious meningeal stimulation by the irritant capsaicin triggered trigeminovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Pre-clinical studies in migraine animal models have shown that topiramate inhibited neurogenic dural vasodilation by inhibiting CGRP release from pre-junctional trigeminal neurons induced by noxious inoculation (17, 51). We also found that topiramate inhibited CGRP immunoreactivity in the trigeminal ganglia and dura (23, 24) of rats in a capsaicin-stimulated migraine model (22). Topiramate has been also reported to enhance GABA currents of GABA A receptors, including the α6 subunit-containing GABA A receptors (α6GABA A Rs) (52).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Pre-clinical studies in migraine animal models have shown that topiramate inhibited neurogenic dural vasodilation by inhibiting CGRP release from pre-junctional trigeminal neurons induced by noxious inoculation (17, 51). We also found that topiramate inhibited CGRP immunoreactivity in the trigeminal ganglia and dura (23, 24) of rats in a capsaicin-stimulated migraine model (22). Topiramate has been also reported to enhance GABA currents of GABA A receptors, including the α6 subunit-containing GABA A receptors (α6GABA A Rs) (52).…”
Section: Discussionmentioning
confidence: 67%
“…Thus, CGRP is believed to be a potential biomarker of migraine (1121). Pre-clinical studies have shown that trigeminal activation can induce CGRP release from peri-vascular nerve endings (2224), resulting in pia vessel dilatation, leading to migraine (17). Moreover, CGRP antagonists can reduce cortical spreading depression, which is believed to be an important pathogenic manifestation of migraine with aura (18, 20, 21), in animal models of migraine.…”
Section: Introductionmentioning
confidence: 99%
“…Szolcsanyi 23 analyzed the depletion of sensory neurons by capsaicin and the relation of neuropeptides released in the analysis of the diameter of the cranial arteries, to verify whether there was dilation. Huang et al 27 observe that chemical stimulation with capsaicin also influences the release of CGRP assessed immunohistochemically through the polyclonal antibody of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Although conclusive evidence is still needed, one may hypothesize that the abovementioned mechanisms related to TRP channels contribute to the decreased release of CGRP associated to BoNTA; initial evidence of the role of this circuitry has also been emerging for other drugs. Both valproic acid and topiramate have been shown to inhibit the capsaicin-induced elevation of CGRP immunoreactivity in the trigeminal ganglia and CGRP depletion in the dura mater of rats, even if with some differences among adult and pediatric rats [136]. Finally, the pretreatment with valproic acid has been shown to attenuate the enhanced blood flow responses observed after inhalation of the TRPA1 agonist acrolein in a rodent model of chronic migraine [111].…”
Section: Bonta Cgrp and Trp Channelsmentioning
confidence: 99%